Detection and identification of 16SrI-B and a novel 16SrI phytoplasma subgroups associated with leaf malformation of Cucurbita moschata (pumpkin) in Malaysia - Tennakoon, T. M. N. D.; Naderali, N.; Kong, L. L.; Ahmad, K. B.; Vadamalai, G. (Springer Nature, 2022)
Pumpkin vines (Cucurbita moschata) exhibiting symptoms of shortened internodes and stunting of the vine were observed in vegetable farms in the state of Selangor, Malaysia. Nested PCR assay with 16SrRNA gene specific primers proved the presence of phytoplasma DNA in all symptomatic samples. BLAST analysis of 16SrRNA gene sequence of the pumpkin phytoplasma isolates showed 99% sequence identity with the Cucurbita pepo ‘witches’ broom phytoplasma (16SrI). In addition, virtual RFLP analysis of 16SrRNA gene sequence and the phylogenetic tree analysis confirmed that the phytoplasma detected in one symptomatic sample could belong to a new sub group of 16SrI from the previously recognized sub groups of 16SrI group by the HinfI profile whereas other phytoplasmas detected in symptomatic samples tentatively sorted as a member of 16Sr group I, subgroup B.